Tingkat Pengetahuan Siswa dalam Pembelajaran Permainan Bola Voli di SMP Pasundan - Junaedi Malik Ibrahim; Rina Marlina; Rekha Ratri Julianti (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine the knowledge of students in learning volleyball games for class VII students of SMP Pasundan. To answer the formulation of the problem that has been formulated, the author uses descriptive quantitative research, the method used in this research is a survey. This research was conducted at Pasundan Junior High School by taking all VII graders, totaling 4 classes. However, the sample in this study were 31 students from another school, namely MTS Al-Kautsar, each of which was taken randomly per class. The instrument used is multiple choice questions. The results of this study indicate that students' knowledge in learning volleyball games for seventh grade students of SMP Pasundan is high with consideration of the highest frequency being in the high category with 51 students or 36%. Students' knowledge in learning volleyball games for seventh grade students of SMP Pasundan which is categorized as very high 1 student or 1%, high 51 students or 36%, moderate 44 students or 31%, low 33 students or 23%, very low 13 students or 9% .